نقد نظرية اختلاف الاسانيد عند الحداثيين كتاب من -اسلام القرآن الى اسلام الحديث لجورج طرابيشي أنموذجا - مداس, خديجة (University Of Eloud جامعة الوادي, 2019)
تتناول هذه الدراسة موضوع "نقد نظرية اختلاق الأسانيد عند الحداثيين-جورج طرابيشي أنموذجًا-"، حيث تهدف إلى كشف شبهة جورج طرابيشي التي يعتبر من خلالها أن الأسانيد الحديثية إنما هي من وضع وتركيب الرواة في وقت متأخر عن زمن النبوة، فهي محض كذبٍ وافتراء كما بينتْ مدى تأثر الحداثيين بالفكر الاستشراقي، فكانت دعوى الاختلاق كنموذجٍ عن تبنيهم الكامل لأفكار المستشرقين وإحياء أطروحاتهم حول الإسلام عمومًا، والسنة النبوية خصوصًا، وقد تمّ في الجزء الأخير من البحث عرض المستندات التي اعتمدها طرابيشي لإثبات اختلاق الأسانيد الحديثية من خلال النصوص التي أوردها في كتابه" من إسلام القرآن إلى إسلام الحديث" ثم الإجابة عنها اعتمادا على أقوال الباحثين، والرد على هذه النظرية انطلاقا مما شهد به واقع الروايات الحديثية. This study deals with the topic "Critique of the theory of fabricating the foundations of the modernists - George Tarabishi as a model -", where it aims to reveal the suspicion of George Tarabishi through which the modern evidence is that it was the status and composition of narrators late in the time of the prophecy, as they are pure lies and slander as It showed the extent of the modernity's influence on Orientalist thought, so the case of fabrication was a model for their full adoption of the ideas of the Orientalists and the revival of their theses on Islam in general, and the Sunnah of the Prophet in particular. In the last part of the research, the documents adopted by Tarabishi to prove the fabrication of modern hadiths were presented through the texts he mentioned in His book, "From Islam of the Qur’an to Islam of Hadith," then answering it based on the scholars' statements, and responding to this theory based on what the reality of modern narrations attested to.
مذكرة ماستر تخصص علوم الحديث
Keywords: الاسناد-نظرية الاختلاق- جورج طرابيشي-تراكمية الأحاديث-قانون النسيان; Attribution - the theory of fabrication - George Tarabishi - cumulative hadiths - the law of oblivion